Pengaruh Media Pembelajaran Pembangkit Listrik Tenaga Air Mini Terhadap Kemampuan Argumentasi Siswa - Wajdi, Moh Nasrul; Sukroyanti, Baiq Azmi; Gummah, Syifa'ul; Zuhdi, Iskandar (Universitas Pendidikan Mandalika, 2025)
Low argumentation skills in physics classrooms motivate practice-based instruction. This quasi-experimental study tested whether a mini hydropower instructional medium improves students’ argumentation skills. Using a Non-Equivalent Control Group Design, two Grade 10 science classes at SMA TI NWDI Wanasaba participated (n = 21 per class). Class X IPA 1 used the mini hydropower medium, while Class X IPA 2 received regular instruction. Instruments comprised a teaching module, observation sheets, and an argumentation pre-test and post-test aligned with the Toulmin Argument Pattern. Normality and homogeneity assumptions were met. Pre-test means were 34.05 (experimental) and 31.00 (control). Post-test means were 78.05 and 76.57, respectively. A one-tailed independent-samples t test showed a statistically significant difference at α = .05, with t = 4.23 exceeding the critical value of 1.72. The findings indicate that integrating a mini hydropower instructional medium can enhance students’ argumentation skills in high-school physics. For interpretive caution, future studies should analyze gain scores or apply ANCOVA to adjust for baseline differences, report effect sizes and confidence intervals, and document instrument validity and reliability. The study suggests that authentic, hands-on energy contexts can provide a productive platform for students to formulate claims, marshal evidence, and articulate warrants in physics reasoning.